2007
DOI: 10.1111/j.1475-4762.2007.00721.x
|View full text |Cite
|
Sign up to set email alerts
|

Second homes, community and a hierarchy of dwelling

Abstract: The word 'dwelling', to dwell, supposes engagement, in the sense that those who dwell are seen to engage with others and, in doing so, contribute to social capital and cohesion expressed in the forming of 'community'. Second home buying may be viewed as a course of action severing the process-product link between dwelling and community, as a brake on the community building process. In this paper, I contrast the view of dwelling as process -and its coupling with the 'traditional' place-community -with alternat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 5 publications
0
45
0
3
Order By: Relevance
“…Strangely, there is also a phenomenological basis to this pejorative view of second homes, building on the work of Heidegger once again, it might be suggested that second home owners have a tendency to engage in "private" (King 2004), rather than in more active forms of public or collective dwelling. Gallent (2007) argues that these latter forms (which are a corruption rather that an extension of Heidegger's thinking) have, in debates concerning community development and mutualism, been viewed as superior to the seemingly closed and inert nature of private dwelling. Moreover, the policy imperative to build "sustainable communities" (through British planning and local government policies and programmes in the example cited by Gallent) has led to the construction of a "hierarchy of dwelling", with clearly "active citizens" -who contribute in measurable ways to an agreed "stable" culture (King 2004, 23) -being endowed with greater legitimacy and morale rights.…”
Section: New Forms Of Consumption Residence and Dwellingmentioning
confidence: 99%
See 3 more Smart Citations
“…Strangely, there is also a phenomenological basis to this pejorative view of second homes, building on the work of Heidegger once again, it might be suggested that second home owners have a tendency to engage in "private" (King 2004), rather than in more active forms of public or collective dwelling. Gallent (2007) argues that these latter forms (which are a corruption rather that an extension of Heidegger's thinking) have, in debates concerning community development and mutualism, been viewed as superior to the seemingly closed and inert nature of private dwelling. Moreover, the policy imperative to build "sustainable communities" (through British planning and local government policies and programmes in the example cited by Gallent) has led to the construction of a "hierarchy of dwelling", with clearly "active citizens" -who contribute in measurable ways to an agreed "stable" culture (King 2004, 23) -being endowed with greater legitimacy and morale rights.…”
Section: New Forms Of Consumption Residence and Dwellingmentioning
confidence: 99%
“…It has been suggested that the alleged introversion of second home owners (or their long-term absence from host communities) may act to limit the scope of social interactions and therefore their contribution to community building (Gallent 2007; but see Huijbens 2012, for a counter-view). The extent to which a community is "built", through this interaction (Falk and Kilpatrick 2000), may be expressed in terms of the accumulation of "social capital" or the "resource potential of social relationships" (Agnitsch, Flora, and Ryan 2006, 36).…”
Section: Patterns Of Residence and Social Capitalmentioning
confidence: 99%
See 2 more Smart Citations
“…S druge strane, pretpostavka je da stalni stanovnici imaju dugoročan i ekonomski orijentiran odnos prema ruralnom prostoru u kojem žive (Green i dr., 1996;Gallent, 2007). S obzirom na tu okolnost, odnos između lokalnog i privremenog stanovništva često se interpretira kao antagonizam koji proizlazi iz različitih interesa unutar istog prostora koji mogu dovesti do određenih konflikata.…”
Section: Sekundarno Stanovanje I Lokalna Zajednicaunclassified